1952
DOI: 10.1002/jctb.5010020901
|View full text |Cite
|
Sign up to set email alerts
|

Ideal copolymers and the second‐order transitions of synthetic rubbers. i. non‐crystalline copolymers

Abstract: Theoretical and practical evidence is put forward to show that copolymers can be treated like solutions of small molecules in the interpretation of packing phenomena, and that ideal volumeadditivity of the repeating units in copolymers is frequently realized. On this basis equations are derived for predicting 0, the second-order transition temperature, of binary copolymers from the two second-order transition temperatures of the pure polymers and their coefficients of expansion in the glassy and rubbery states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
881
2
13

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,330 publications
(935 citation statements)
references
References 24 publications
39
881
2
13
Order By: Relevance
“…Modelling of the glass transition data was performed using the Gordon-Taylor equation 31 , from which it was confirmed that a positive correlation between glass transition temperature and weight fraction of p(HEMA) existed. Based on this information it may be concluded that the hydrogels were copolymers and not polymer blends 36 .…”
Section: Physicochemical Properties Of Hydrogelsmentioning
confidence: 93%
“…Modelling of the glass transition data was performed using the Gordon-Taylor equation 31 , from which it was confirmed that a positive correlation between glass transition temperature and weight fraction of p(HEMA) existed. Based on this information it may be concluded that the hydrogels were copolymers and not polymer blends 36 .…”
Section: Physicochemical Properties Of Hydrogelsmentioning
confidence: 93%
“…d From Lienhard et al (2012a). e Based on a Gordon-Taylor fit (Gordon and Taylor, 1952) between T g of levoglucosan and T g of NH 4 HSO 4 taken from Zobrist et al (2008). f From Lienhard et al (2012b).…”
Section: A2 Parameterization Of D W (T a W )mentioning
confidence: 99%
“…29,35 Different derivations of Eq. (9) are based on different physical interpretations of the parameters k i .…”
Section: Introductionmentioning
confidence: 99%